Prevalence of Veterinary and Zoonotic Helminths in Sheep from Livestock Markets and Abattoirs in Gombe State, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
A cross-sectional study was conducted between May 2023 and June 2024 to determine the prevalence and distribution of veterinary and zoonotic helminths among sheep sourced from livestock markets and abattoirs in Gombe State, Nigeria. Using a two-stage sampling approach, a total of 650 sheep were examined across six locations—four livestock markets (Gombe Central, Kwadom, Dukku, and Kumo) and two abattoirs (Gombe Main and Bajoga). Of these, 516 were infected, yielding an overall prevalence of 79.4% (95% CI: 76.1–82.3). Infection rates were higher in abattoirs (87.2%) than in markets (71.8%). Nematodes predominated (58.9%), with Haemonchus contortus (38.0%), Trichostrongylus spp. (18.9%), and Strongyloides papillosus (2.0%) as the principal species. Trematode infections accounted for 17.4%, mainly Fasciola gigantica (11.1%) and Paramphistomum spp. (6.3%), while the cestode Moniezia expansa occurred in 3.1% of cases. Age, body condition, breed, and season significantly influenced prevalence (p < 0.0001), with adults, poorly conditioned sheep, the Yankasa breed, and rainy-season samples showing the highest infection rates. Sex had no significant effect (p = 0.057). Notably, zoonotic helminths constituted 51.1% of all infections, emphasizing potential public health implications. The predominance of H. contortus and F. gigantica underscores the need for integrated helminth control strategies, improved management, and routine surveillance at the livestock–human interface in Gombe State.